Ascertaining the Transfer of Facility Management Knowledge to the Development of New Students' Residential Colleges in UTHM Malaysia - Adeyemi, Ifeoluwa Adedoyin; Martin, David; Eni, Sabariah; Adeyemi, Adegbenga (Journal of Technology Management and Business, 2019)
Facility management (FM) knowledge has been deemed beneficial because it arises from the use and operation of buildings. Transferring the knowledge from old buildings to new ones will ensure that maintenance problems which occur as a result of poor design decisions will be avoided. Despite the numerous benefits that stem from the transfer of FM knowledge, existing literature has revealed that FM knowledge is rarely included in the design of new buildings. To combat this, a typology was created to identify mechanisms needed for the transfer of FM knowledge to new buildings. This study adopted this typology to ascertain the transfer of FM knowledge to new students' residential colleges in UTHM Malaysia. The qualitative case study design was used to obtain data by interviewing selected individuals that played key roles in the development of the new students' residential colleges in UTHM. When compared to the old students' residential colleges, study findings revealed a decline in the transfer FM knowledge to new students' residential colleges. This was basically as a result of the fact that the new students' residential colleges were built by private developers. Problems with the current transfer process for FM knowledge were revealed, and suggestions were made for improvements.